OCCASIONAL DERIVATIVES IN CREATIVE EPICS - Adizova Nilufar Istamovna (Galaxy International Interdisciplinary Research Journal, 2022)
The Hero of Uzbekistan, the honored poet of the Uzbek people - Erkin Vahidov is a creator who has won the hearts of the people with his deep thoughts, philosophical observations and eloquence. The poet’s jeweled approach to the word shows that he has a unique skill. In his work, each word is sealed in its place in the form of an eye on a ring.This article discusses the unique examples of new units of expression - occasional products, created by the poet in a creative approach to language units, which contributed to the enrichment of the treasury of the Uzbek language, using the example of his epics. In this way, comments are made on the fact that the possibilities of our language know no boundaries.